The psychometric properties of the Bergen–Yale sex addiction scale for the Iranian population - Youseflu, Samaneh (BMC Psychiatry, 2021)
BACKGROUND: The assessment of sex addiction among different populations requires a valid and reliable tool. Since the Bergen–Yale Sex Addiction Scale (BYSAS) was not available in Iran, this study aimed to evaluate the validity and reliability of the Persian version of the BYSAS. METHODS: After translation/back-translation procedure, a total of 756 Iranian men and women completed the BYSAS. The structural validity of this tool was evaluated by exploratory and confirmatory factor analyses. An expert panel review also examined content validity of the items. Psychometric properties of the scale including validity, reliability (internal consistency [Cronbach’s alpha]) and test-retest) and factor structure were assessed. RESULTS: Content Validity Index (CVI) and Content Validity Ratio (CVR) scores for the BYSAS were 0.75 and 0.62, respectively. In the measure’s structural validity, the results of exploratory and confirmatory factor analysis supported the One-factor structure. Data analysis demonstrated satisfactory internal consistency (Cronbach’s alpha ranging from 0.88 to 0.89). DISCUSSION: Study findings suggest that the BYSAS is a valid and reliable instrument for assessing sex addiction among Persian speaking adults. Replication of research findings is needed to expand the BYSAS for clinical and non-clinical Iranian populations.